Waterlily Leafcutter, Synclita obliteralis (Walker) (Insecta: Lepidoptera: Crambidae: Acentropinae) - Dale H. Habeck; James P. Cuda (EDIS, 2009)
EENY-424, a 4-page illustrated fact sheet by Dale H. Habeck and James P. Cuda, is part of the Featured Creatures collection. It describes this common moth that has been observed to inflict severe damage on the invasive aquatic plant Hygrophila polysperma — its distribution, description, life cycle and biology, hosts, economic importance, and related species. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.